Significance of micronutrients in defense to white rust and improvement of yield parameters of Indian mustard [Brassica juncea (L.) Czern and Coss.]: MICRONUTRIENTS FOR WHITE RUST AND IMPROVEMENT OF YIELD PARAMETERS OF INDIAN MUSTARD - ANNU; OM PARKASH; A S RATHI; R AVTAR (Journal of Oilseeds Research, 2026)
The study aimed to assess the potential of micronutrients to enhance resistance to white rust disease and improve yield parameters in Indian mustard. Field experiments were conducted with the application of different micronutrients, both individually and in combination. Observations on white rust severity (%), staghead incidence (%), seed yield (kg/ha), and yield attributes were recorded. The minimum white rust severity (31.11%), staghead incidence (4.44%), and highest seed yield (2228.55 kg/ha) were observed with the soil application of gypsum @ 250 kg/ha + borax @ 10 kg/ha + CuSO4 @ 19 kg/ha + NaMoO4 @ 1.1 kg/ha at 30 DAS, compared with white rust severity (45.83%), staghead incidence (6.09%), and seed yield (1779.79 kg/ha) in the control treatment. Yield attributes, viz., the maximum number of primary branches per plant (5.83), secondary branches per plant (12.33), main shoot length (90.93 cm), number of siliquae on the main shoot (62.60), and number of seeds per siliqua (12.53), were also recorded under this treatment combination. Plant height, siliqua length, oil content, and 1000-seed weight did not vary significantly among the treatments. Micronutrient application was found to be highly effective in reducing white rust severity and staghead incidence during both the leaf and staghead phases. Thus, micronutrient application contributed to minimizing yield losses and enhancing resistance to white rust in Indian mustard, thereby supporting eco-friendly and sustainable agriculture.